Neoliberalism and changing regional policy in Australia - McKenzie, Fiona Haslam; Tonts, M. (Routledge, 2005)
This paper examines the role of neoliberalism in shaping Australian federal regional development policy over the past three decades. As in other parts of the world, since the 1980s Australian federal governments have tended to favour the role of market forces, as opposed to direct intervention in regional development. By the 1990s, however, the negative social and economic impacts of neoliberal approaches, together with a widespread electoral backlash, contributed to an adjustment in the direction of regional development policy. We argue that this transition is reflective of a wider shift in neoliberal politics, whereby limited government intervention and institution building are increasingly seen as appropriate policy responses. While in part this is linked to the shortcomings of previous policy approaches, it is also apparent that political opportunism is an important element of this shift.